Orientation-lycée, vecteur de changement organisationnel et culturel - Ferré, Danielle (Canadian Journal of Counselling and Psychotherapy, 2007)
Students and families experience a great need for education about school guidance. Teachers and school administrators also recognize this need. In response, an action research study entitled 'Orientation-Lycée' (emphasis on secondary schools) was conducted. This methodological approach enabled students to develop the specific skills required for building and monitoring their own guidance process. This approach is also a suitable vehicle for change in schools, which are regarded as self-transforming organizations.